(untitled) (Journal of Nepal Physical Society, 2022)
In this work, dust properties around the White Dwarf PG 1225-079 located at RA (J2000): 12h 27m 47.35s, DEC(J2000): -08° 14’ 37.97” is studied extensively using the publicly available data from Improved Reprocessing of IRAS Survey (IRIS), AKARI infrared survey and Wide field Infrared Survey Explorer (WISE). The bipolar dust structure hardly resolved in IRIS (60 μm and 100 μm) is clearly resolved in AKARI (90 μm and 140 μm) and WISE (12 μm and 22 μm) images. The dust color temperature and dust mass are calculated from the infrared flux density. The average value of dust color temperature in isolated dust structure is 27.57 K for IRIS (I1). For isolated upper and lower dust clouds the average temperatures are; 22.64 K and 22.63 K for AKARI (A1 and A2), 295.34 K and 296.85 K in WISE (W1 and W2) data. A wide range of temperatures suggests the bipolar dust structure is dynamically active. The mass of dust is found to be 3.44 × 1025 kg in IRIS (I1), 1.82 × 1026 kg and 5.89×1026 kg in two bipolar regions in AKARI (A1 and A2) and 1.12 ×1026 kg and 1.14×1026 kg in WISE (W1 and W2). A good relation is found between the infrared flux in all survey data with r2 value 0.83 in IRIS (I1) and more than 0.90 in AKARI (A1, A2) and WISE (W1, W2) data. SIMBAD database explore some sources including Supernova Remnants nearby the dust which might be the progenitor of dust as well as the contributor of energetic radiation. The Gaussian modeling of temperature is found to be deviated from normal shape. The contour plot of dust color temperature and dust mass shows non uniform variation among the IRIS, AKARI and WISE survey. The relation between infrared flux, dust color temperature and dust mass within the dust clouds are presented.